Perceptions of Portuguese teachers about sex education - Ramiro, Lúcia; Matos, Margarida Gaspar de (Revista de Saúde Pública, 2008)
OBJECTIVE: To assess perceptions and attitudes regarding sex education among middle and high school teachers in Portugal. METHODS: A study comprising 371 middle and high school teachers, both female and male, was conducted in Portugal in February and March 2006. Data was collected through snowball technique. The questionnaire was made up of two parts: the first collected data on demographics, career, religious background and training and experience in sex education; the second part presented three measures related to sex education, one assessed attitudes, another importance given to sex education, and the third the grade at which respondents believed sex education topics should be taught. The analysis of differences between gender, trained and untrained teachers in sex education, and experienced and non-experienced teachers in teaching sex education was carried out using ANOVA. RESULTS: Overall, teachers showed a fairly straightforward attitude towards sex education and assessed it as moderately/highly important. Body image was found to be the only topic that should be introduced in the 5th and 6th grades. Female teachers [F(1;366)=7.772;p=.006], trained teachers [F(1;351)=8.030; p=.005] and experienced teachers in teaching sex education [F(1;356)=30.836;p=.000] showed a more positive attitude towards sex education (M=39.5; 40.4; 41.3; respectively). Only trained teachers assessed its teaching as highly important [F(1;351)=5.436;p=.020]; and female teachers believed it should be introduced earlier [F(1;370)=5.412;p=0.021]. CONCLUSIONS: In general, teachers favor sex education in school. The fact that most topics of sex education are only taught in the 5th-6th or 7th-9th grades may have serious consequences since sex education has to be introduced before students engage in sexual behaviors.